Nutritional impact on Immunological maturation during Childhood in relation to the Environment (NICE): A prospective birth cohort in northern Sweden - Barman, M.; Murray, F.; Bernardi, A.; Broberg, K.; Bolte, Sven; Hesselmar, B.; Jacobsson, B.; Jonsson, K.; Kippler, M.; Rabe, H.; Ross, A.; Sjöberg, F.; et al. (BM J Group, 2018)
© Author(s) (or their employer(s)) 2018. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ. Introduction Prenatal and neonatal environmental factors, such as nutrition, microbes and toxicants, may affect health throughout life. Many diseases, such as allergy and impaired child development, may be programmed already in utero or during early infancy. Birth cohorts are important tools to study associations between early life exposure and disease risk. Here, we describe the study protocol of the prospective birth cohort, 'Nutritional impact on Immunological maturation during Childhood in relation to the Environment' (NICE). The primary aim of the NICE cohort is to clarify the effect of key environmental exposures - diet, microbes and environmental toxicants - during pregnancy and early childhood, on the maturation of the infant's immune system, including initiation of sensitisation and allergy as well as some secondary outcomes: Infant growth, obesity, neurological development and oral health. Methods and analysis The NICE cohort will recruit about 650 families during mid-pregnancy. The principal inclusion criterion will be planned birth at the Sunderby Hospital in the north of Sweden, during 2015-2018. Questionnaires data and biological samples will be collected at 10 time-points, from pregnancy until the children reach 4 years of age. Samples will be collected primarily from mothers and children, and from fathers. Biological samples include blood, urine, placenta, breast milk, meconium, faeces, saliva and hair. Information regarding allergic heredity, diet, socioeconomic status, lifestyle including smoking, siblings, pet ownership, etc will be collected using questionnaires. Sensitisation to common allergens will be assessed by skin prick testing and allergic disease will be diagnosed by a paediatrician at 1 and 4 years of age. At 4 years of age, the children will also be examined regarding growth, neurobehavioural and neurophysiological status and oral health. Ethics and dissemination The NICE cohort has been approved by the Regional Ethical Review Board in Umeå, Sweden (2013/18-31M). Results will be disseminated through peer-reviewed journals and communicated on scientific conferences.